CONTEXTUALIZING SOCIAL QUR’ANIC VALUES: COMPARATIVE PERSPECTIVES FROM INDONESIA AND THAILAND - Paison Da-Oh (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2026)
The contextualization of Qur’anic social values has become an important approach for addressing contemporary social challenges in diverse Muslim societies. This study examines how social Qur’anic values are interpreted and contextualized in Indonesia and Thailand, with particular attention to issues of tolerance, social justice, poverty, education, and interreligious relations. Employing qualitative library research and a comparative approach, the study analyzes scholarly discussions on social Qur’anic interpretation and its development within the socio-cultural and political contexts of both countries. The findings reveal that the contextualization of Qur’anic social values in Indonesia tends to emphasize pluralism, religious moderation, democratic coexistence, and national harmony, reflecting the position of Muslims as the majority within a multicultural society. In contrast, the contextualization of these values in Thailand, particularly among the Muslim community of Pattani, is primarily directed toward strengthening Islamic identity, communal solidarity, and peaceful coexistence within a minority-Muslim environment. These differences demonstrate that the interpretation of social Qur’anic values is closely shaped by local historical experiences, cultural traditions, social structures, and political realities. The study argues that social Qur’anic interpretation in Southeast Asia is dynamic and context-sensitive, serving not only as a religious discourse but also as an ethical framework for responding to contemporary social issues. By highlighting comparative experiences from Indonesia and Thailand, this research contributes to the development of contextual Qur’anic studies and enriches broader discussions on Islam, society, and social transformation in Southeast Asia.